1968
DOI: 10.3109/02770906809100348
|View full text |Cite
|
Sign up to set email alerts
|

Aerogenic BCG Vaccination Against Tuberculosis in Animal and Human Subjects

Abstract: Aerosol vaccination against tuberculosis is as old as the disease itself. There can be no question that T-irulent tubercle bacilli have been aspirated over the milleniums and have been a great factor in increasing our resistance against virulent tubercle bacilli. The danger, however, of aspirating virulent tubercle bacilli is that there is always the possibility of developing progressive disease; and furthermore, once a virulknt organism lodges in the body, it remains a constant source of danger to the host. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…Our results compare favorably with the work of Rosenthal et al (17) and Lagranderie et al (18). In the pioneering work by Rosenthal et al in 1968 (17), guinea pigs, children, and medical students were exposed to BCG aerosols generated by nebulization.…”
Section: Discussionsupporting
confidence: 91%
“…Our results compare favorably with the work of Rosenthal et al (17) and Lagranderie et al (18). In the pioneering work by Rosenthal et al in 1968 (17), guinea pigs, children, and medical students were exposed to BCG aerosols generated by nebulization.…”
Section: Discussionsupporting
confidence: 91%
“…They support M. tuberculosis challenge studies in macaques and guinea pigs that have shown aerosol administration of BCG to be more protective than parenteral (p.) vaccination (10,11). BCG has also been given as an aerosol to healthy adults and children and repeatedly to patients with metastatic lung disease (12)(13)(14). Respiratory function tests and postmortem examination of cancer patients administered BCG by aerosol indicated no significant pulmonary dysfunction or disseminated BCG infection (13,14).…”
mentioning
confidence: 65%
“…Finally, BCG vaccination of human subjects by the respiratory route has been reported to be well tolerated and to result in tuberculin conversion in a majority of vaccines (18,19). While the potential for vaccination of humans by the respiratory route is unclear, it is worth emphasizing that mice immunized and challenged by the aerosol route exhibited an intense cellular response to the challenge that subsided during the 6 weeks after challenge.…”
Section: Discussionmentioning
confidence: 99%